Three-dimensional microstructure evolution and mechanical behavior of nanoporous Cu foams. (July 2016) - Nam, Seung Jin; Hwang, Jun Yeon; Kim, Heung-Kyu; Choi, Hyun Joo
Abstract: Nanoporous Cu foams having various pores and strut size were fabricated by chemical dealloying process with Al-Cu precursors. Microstructural evolution of three-dimensional configuration was investigated by electron microscopes aided focused ion beam (FIB) technique. The specific surface area and strength of the Cu foams increased with decreasing pore and strut sizes. The measured strength and specific surface areas were correlated with the Exner-Pohl model by modifying the parameters using the microstructural observation. The modified model demonstrated the mechanical behaviors of nanoporous Cu foams accounted for the strut size and the deformation-twinning model. Graphical abstract: SEM image and 3D reconstruction aided FIB slices of the Cu nanofoams dealloyed from Al-Cu system.